Multicomponent crystals of gliclazide and tromethamine: preparation, physico-chemical, and pharmaceutical characterization*. (1st February 2018) - Bruni, Giovanna; Berbenni, Vittorio; Maggi, Lauretta; Mustarelli, Piercarlo; Friuli, Valeria; Ferrara, Chiara; Pardi, Francesca; Castagna, Federica; Girella, Alessandro; Milanese, Chiara; Marini, Amedeo
Abstract: Objective: To improve the pharmaceutical behavior of the oral antidiabetic agent gliclazide through the synthesis of multicomponent crystals with tromethamine. Methods: Multicomponent crystals were prepared by solvent evaporation method, kneading, and combining mechanical and thermal activation. DSC, FT-IR spectroscopy, X-ray diffraction, SEM-EDS, and SSNMR were used to investigate their formation. Measurements of solubility and dissolution rate were carried out for the pharmaceutical characterization. Results: The formation of multicomponent crystals of gliclazide and tromethamine was confirmed by all the techniques. In particular, FT-IR and NMR measurements revealed that the interaction between drug and coformer leads to significant changes of the hydrogen bond scheme, and that almost all the functional groups of the two molecules are involved. The dissolution profile of the new phase is significantly better than that of both pure gliclazide and of the reference commercial product Diabrezide ® . Conclusions: The new system shows an improved pharmaceutical behavior and could be formulated in a dosage form to obtain a rapid and complete release of the drug available for absorption.